A Novel Technique for the Three-Dimensional Visualization of Tissue Defects Using Tissue Paper Models: Spatial Analysis for Reconstruction Assessment Method - Triatmoko, Sara E.; Siburian, Elida S.; Sudarman, Jesica P. (Journal of Reconstructive Microsurgery Open, 2025)
This technical note presents an innovative technique that uses tissue paper to create three-dimensional (3D) models to visualize tissue defects. This approach allows the construction of detailed, anatomically accurate models that significantly enhance surgeons' and medical professionals' comprehension of tissue damage in various clinical scenarios.The key aspects of this technique include assessing the location and size of the defect, selecting an appropriate donor site, and designing the flap using tissue paper at the recipient site before refining it to match the donor site. Different flap designs, such as local, regional, and free flaps, are used, each offering distinct advantages and limitations depending on the clinical context.This technique is straightforward, cost-effective, and highly adaptable, making it an invaluable tool for both preoperative planning and educational purposes. Meticulous attention to detail is essential for flap design because it directly influences the success of the procedure. Critical factors, such as tissue laxity, scar orientation, and aesthetic subunits, must be carefully considered to ensure optimal wound healing and cosmetic outcomes.In summary, the use of tissue paper to create 3D models is a valuable technique that enhances the understanding and planning of surgical interventions for tissue defects, ultimately improving clinical outcomes.
Keywords: flap design; reconstruction assessment; tissue defect; flap surgery; sterile tissue paper